Post-independence experience in the Caribbean, the Guyana case in particular - Kwayana, Eusi (Working People's Alliance GeorgetownGY, 1987)
Argues that the characteristics of the pre-independence struggle such as the class struggle influenced the kind of post-independence life in the Caribbean. Reviews the role of labour, trade unions, and the petty bourgeoisie in Guyana. Discusses dictatorship in Guyana and the failure of formal democracy in the Caribbean. Raises questions facing the Caribbean political community which relate to the improvement in the quality of economic life of the masses, racial equality, the role of women and the treatment of indigeneous peoples.